Analisis Faktor-Faktor yang Mempengaruhi Ekspor Alas Kaki Indonesia ke Amerika Serikat - Mariati, Nayah (PPJP ULM, 2018)
This study was conducted to determine Factors Affecting Indonesia’s footwearexport to the United States and to know which variables are most influential infootwear exports. The location of this research is in Indonesia, and the data source used issecondary data obtained from The Indonesian Central Bureau of Statistics, WorldBank, and Bank Indonesia where the data are analyzed using multiple linearregression model to determine whether the variables of footwear export such asexchange rate, the gross domestic product of the United States, and the inflation setaffect to the export of Indonesian footwear. The results of this study indicate that the variables of the exchange rate, USGDP, and inflation simultaneously have a significant effect on the export ofIndonesia’s footwear that can be seen from the test f that obtained considerable value.A partial test of a variable of the exchange rate and inflation show insignificant resultbecause when the exchange rate or inflation weakens, the price will rise; hence exportwill decrease. Still, the cost of the competitor's country exports also increases, theprice of Indonesian goods becomes less expensive. Export destination countries ofIndonesia will continue to purchase products while for the US GDP variables showedsignificant results because when the United States income increased, then thepurchasing power of the community also increased and positively affected the exportof